CYBERPANOPTIC: EKSPERIMENTASI DAN (TRANSPARANSI) KUASA PENGAWASAN - Hery Prasetyo (LITERASI: Indonesian Journal of Humanities, 2013)
The article focuses issue of cyberspace with question “how subjects reproduce their presence in technological space?” Technological space is a space that is created through information or internet tehcnology network development. Internet booming in Indonesia’s social movement historicity attached with problem of information spreading under authoritarian New Order Regime that systematically placed truth which is controlled and centered. In this point, internet is able to uncover order and naration of truth from the ruler. But internet became ironic when its presence brought consequences into mass subjectivity presence space, fluid in up to speed technology and the will of becoming in experimentation form without limits. Experimentation which referred to subject’s textuality and visuality is presented as consciousness tendency in political order and at the same time, represented cultural dimension that discursively appeared to negate in virtual partial objectivity. This condition, for writer, is part of spatiality which signify the presence of subjectivity that is formed in late capitalism order. The order is able to touch social unconsciousness space. Especially, on how kinds of presence which are placed as selfconsciousness particularity are only become kinds of language representations without refer to materiality formation movement that were represented. Keywords: experimentation, power of surveillance, politic of presence, virtuality